Honduras : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This paper describes economic developments in Honduras during the 1990s. During 1990-93, Honduras adopted an economic program aimed at reducing macroeconomic imbalances and at greater openness and efficiency of the economy. Important structural reforms were carried out in the public, financial, and external sectors, and economic activity and nontraditional exports increased at a fast pace. However, the adjustment of macroeconomic imbalances was short lived as the fiscal deficit rose sharply in the run-up to the presidential elections of November 1993.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet